Studi Antibodi Poliklonal Anti-TBC dan Potensinya sebagai Rapid Test Kit pendeteksi TBC - Muzaijadah Retno Arimbi (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2016)
Tuberculosis (TB) is one of the long-known diseases and is still the leading cause of death in the world. A variety of detection methods have been and are being implemented in order to suppress TB prevalence. The aim of this study was to isolate protein from serum pulmonary tuberculosis patients with sputum BTA (+), isolate protein from serum pulmonary tuberculosis patients with sputum BTA (-), and to know the level of antibody specificity in serum pulmonary tuberculosis patients with sputum BTA (+) and serum pulmonary tuberculosis patients with sputum BTA (-). The type of research used was laboratory experimental in Wistar rat experimental animals with Control Group Post Test Design research design. The research design was used with 3 different treatment groups, ie Control Group (without treatment), Group I (treated with isolate protein from serum of Pulmonary TB patients with sputum BTA (+)), and Group II (treated with protein isolate from serum of Pulmonary TB patient with sputum BTA (-) From collected data After dot blot is complete, tabulation of diagnostic test result (dot blot.) To obtain a standard in assessing the results of dot in each of these studies used CorelPhotopaint X4 program to obtain accurate data about the thickness of thin black spots (nilaimean) on the nitrocellulose membrane quantitatively.The data collected is processed using software (software) statistics SPSS version 11.5 From the electrophoresis test results of an exciting protein sample m of Pulmonary TB patients with BTA (+) and protein from serum of Pulmonary TB patients with AFB (-), obtained specific protein with molecular weight of 39 kDa. From the serum 1 serum easternbloting test result from pulmonary TB patients with BTA (+) and serum 2 protein derived from serum of Pulmonary TB patients with BTA (-), positive reaction occurred between antibodipoliklonal (anti 39 kDa) and serum protein of Pulmonary TB with BTA (+), or proteins from serum patients with pulmonary TB with AFB (-). The anti-tuberculosis polyclonal antibody in the study appears to be quite sensitive as Rapid tuberculosis detection test, but no specificity as evidenced by statistical calculation has significance> 0.05, so the anti-tuberculosis polyclonal antibody in this study is quite sensitive, but not specifically used as an MTb detection device Keywords: tuberculosis, specific protein, polyclonal antibody, specificity test Tuberculosis (TB) is one of the long-known diseases and is still the leading cause of death in the world. A variety of detection methods have been and are being implemented in order to suppress TB prevalence. The aim of this study was to isolate protein from serum pulmonary tuberculosis patients with sputum BTA (+), isolate protein from serum pulmonary tuberculosis patients with sputum BTA (-), and to know the level of antibody specificity in serum pulmonary tuberculosis patients with sputum BTA (+) and serum pulmonary tuberculosis patients with sputum BTA (-). The type of research used was laboratory experimental in Wistar rat experimental animals with Control Group Post Test Design research design. The research design was used with 3 different treatment groups, ie Control Group (without treatment), Group I (treated with isolate protein from serum of Pulmonary TB patients with sputum BTA (+)), and Group II (treated with protein isolate from serum of Pulmonary TB patient with sputum BTA (-) From collected data After dot blot is complete, tabulation of diagnostic test result (dot blot.) To obtain a standard in assessing the results of dot in each of these studies used CorelPhotopaint X4 program to obtain accurate data about the thickness of thin black spots (nilaimean) on the nitrocellulose membrane quantitatively.The data collected is processed using software (software) statistics SPSS version 11.5 From the electrophoresis test results of an exciting protein sample m of Pulmonary TB patients with BTA (+) and protein from serum of Pulmonary TB patients with AFB (-), obtained specific protein with molecular weight of 39 kDa. From the serum 1 serum easternbloting test result from pulmonary TB patients with BTA (+) and serum 2 protein derived from serum of Pulmonary TB patients with BTA (-), positive reaction occurred between antibodipoliklonal (anti 39 kDa) and serum protein of Pulmonary TB with BTA (+), or proteins from serum patients with pulmonary TB with AFB (-). The anti-tuberculosis polyclonal antibody in the study appears to be quite sensitive as Rapid tuberculosis detection test, but no specificity as evidenced by statistical calculation has significance> 0.05, so the anti-tuberculosis polyclonal antibody in this study is quite sensitive, but not specifically used as an MTb detection device